Literacy Innovation in the Digital Era: Developing Teacher and Student Capabilities in Facing Technological Challenges - Andriani, Agis; Nuraini, Chandra; Rosmala, Dewi; Sulastri, Fera; Silvani, Dea; Belkis, Salma Ayu; Maulina, Rena; Sarah, Siti (Asosiasi Profesi Multimedia Indonesia, 2025)
Background: Exploring the integration of character education, the Merdeka Curriculum, and differentiated learning methods in Indonesian education is essential. Currently, education in Indonesia recognizes the importance of character education, the Merdeka Curriculum, and differentiation in the learning process. Character education aims to shape students' profiles, reflecting the values of Pancasila, which have professional and social implications.Aims: The study aims to explore literacy innovation in the digital era by focusing on developing teachers’ and students’ capabilities in facing technological challenges.Methods: The study employs a qualitative approach, utilizing reflective practice with educators and students to gather insights on current practices and challenges. The reflective practice stage begins with describing the challenges related to literacy in the school environment through interviews with relevant school elements, followed by implementing literacy activities for teachers and students (workshops, writing groups, and English clubs) ultimately, carrying out evaluations by analyzing the impact of activities.Results: Language skills mentoring for students and teacher writing activities as literacy innovation have resulted in written works. Moreover, teachers produced essay frameworks reflecting their views on literacy and their awareness of the necessary use of technology.Conclusion: Literacy innovation can motivate students and teachers to have awareness in literacy. At the end, the outcomes of these activities (books) can contribute to school accreditation scores.